Leak Detection in Pipeline Using Wavelet and Ceptrum Analysis - Makeen, Mohd Amin; Mohd Fairusham, Ghazali; Abdul, malik; Nurul Fatiehah, Adnan (AENSI Journals, 2014)
Piping system is one of the important features in either home of industrial user. It is essential for transporting fluid from a point to another point. For example, for home user, piping systems functioning as carrier for the water from the damp to every home. Whereas, for industrial user, the fluid that is carried are from different type such as water, gas, oil and many more. But due to many reasons, leaks may occur in the pipelines. This paper is focusing on the leakage detection in the pipelines using wavelet on cepstrum analysis. The basic principle is the fact that water spouting out of a leak in a pressurized pipe generates signal, and this signal contains information to whether a leak exists and where it is located. The present transient methods for finding leaks are mainly based upon correlation analysis, where one sensing device is installed at each side of a leak. This method is hard to operate because it needs a lot of operators to operate it due to equipment in different place. To overcome this limitation a pressure transducer is used as the sensing device and ceptrum analysis to show the data obtained.